The managerial qualities, academic requirements and skills training of resort managers in selected resort spots in Region VI a study of effective resort management - Ching, Kristoffer; Loayon, Joey.; Rubas, Ligaya; Tolentino, Jonalyn; Villanueva, Josephine (1998.)
This research entitled "The Managerial Qualities, academic Requirements, and Skills Training : A Study on Effective Resort management" was undertaken to ascertain the needed improvements of beach managers in the discharge of their servces. This covers thirty-three respondents representing the managers and staff of twenty-two beach resorts in Iloilo, Aklan, and Capiz. Questionnaires were distributed with set of inquiries divided into five man topical fields of interest, to wit : managerial functions, marketing information, finance/accounting information, managerial qualities, and training needs. In the management function, the respondents were asked of their organizational structure and the number of their employees. most of the beach resorts are owned and operated by families thus managerial and administrative functions are also rotated and shared between husband and wife. There was also a preliminary inquiry on the topics discussed during thier trainings and seminars. Most of the responded had attended trainings conducted within their resorts. These were mostly on the topics of management, and finance/accounting. In the marketing information, an inquiry was raised on how do they promote their resort in the local, and if warranted, in the national market. Findings show that promotions are mainly anchored on the word-of-mouth and references b the local inhabitants. These resorts do seldom conduct any market research for the usual reason that they have n technical knowledge and no financing resources to be used in the process. In the finance/accounting information, the respondents are asked of their manner of preparing financial statements. The most common financial statement prepared is the balance sheet at year end. They replied that mostly get their financing from their own resources. They did not often times resort to bank loan financing, as this impose high interest rates which they can not afford to pay given their meager income. In the managerial qualities, the respondents were given a set of questions from which they based their evaluation on the quality level of personnel and resource management in their organization. Findings show that most beach managers are task-oriented and profit-oriented and possess a little quality related to being a people-oriented. In the last topical area on training needs, there was a survey on the course and academic areas which are of interest and the respondent are willing to attend to. This would then be used in the further design of the degree offering of Resort Resource Management in the College of Management. Recommendations were subsequently stated at the end of this paper. It highlights the weak points of these resorts and it also gives suggestive points to overcome these weaknesses.
Research Paper (BA 200-Business Research). -- [Iloilo City] : University of the Philippines Visayas - College of Management, March 23, 1998.